Education Based On Sunda Land Wisdom - Nana Sutarna (STKIP Muhammadiyah Kuningan, 2021)
This study aims to describe the diversity of forms of Sundanese wisdom, design strategies for the implementation of Sundanese wisdom in the world of education and arrange a systematic flow scheme in the process of internalizing Sundanese wisdom values ​​in learning activities. By using a qualitative method, an analytical descriptive approach. The harmony of Sundanese people with the natural surroundings results in increasingly complex local wisdom. So a strategy was designed to facilitate the process of implementing Sundanese wisdom values. The discussion is reviewed in depth by making a systematic flow scheme of the internalization process. Then included examples of the application of the internalization of the wisdom values ​​of Sundanese Land in PAUD institutions. This design and scheme is intended to facilitate the reader in implementing Sundanese wisdom values, especially integrating them in the world of education so as to raise the existence of Sundanese wisdom, maintain national identity and live in harmony with a cultured society.